PENINGKATAN HASIL BELAJAR IPA DENGAN PENEMUAN TERBIMBING PADA SISWA KELAS III SD - Marselus, Marselus; Kresnadi, Hery; Salimi, Asmayani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis researchÂ aimed to determine learning outcome of students in sains science in grade III SDN 07 Kapot Bengkayang District that used guided discovery method. The research method that been used was descriptive method with type of Classroom Action Research. This research was done in 2 cycles. The results of research were obtained (1) The ability of teacher to arrange learning draft from cycle I was 3,84 and cycle II was 4,00. (2) The ability of teacher to do learning showed increase from cycle I 3,93 and cycle II was 4,00. (3) The average of learning outcome of student increased from cycle I with score 63,58 became 78,58 in cycle II. The using of guided discovery method the result of students learning outcome.Â Key words : the learning outcome, guided discovery method